Soil macrofauna, mesofauna and microfauna and their relationship with soil quality in agricultural areas in northern Colombia: ecological implications (2022)
Soil fauna is an essential component of the soil ecosystem for maintaining nutrient cycling and biological soil fertility. This study assessed the soil biodiversity (macrofauna, mesofauna, and microfauna) to define strategies for the sustainable management of tropical agricultural soils. The study was carried out in 200 agricultural production units in the Department of Sucre, in northern Colombia. Physicochemical properties (organic matter, nitrogen, phosphorus, and pH) were determined for each soil sample. The Berlesse-Tullgren method was used to determine the composition of macrofauna and mesofauna, while the sown surface plate counting method was applied for microfauna. Community biodiversity was quantified with diversity indices, and Pearson correlation was carried out to determine the relationships between soil fauna and soil quality indicators. For the macrofauna, 1330 individuals were found, distributed in 22 orders and 65 families; the families Tenebrionidae, Formicidae, Staphylinidae, Scarabaeidae and Julide presented the highest abundance and distribution. Mesofauna presented 1,171 individuals, distributed in the classes Arachnida with seven families and Collembola with four families; the Scheloribatidae, Isotomidae and Galumnidae families presented the highest abundance and distribution. The indices of richness, Shannon-Wiener diversity and Simpson dominance indicated that biodiversity was higher for macrofauna. Pearson's correlation indicated significant correlations between soil mesofauna and soil organic matter (R-2 = 0.87; p <= 0.05) and phosphorous (R-2 = 0.70; p <= 0.05). The relationships between fauna and soil chemical properties indicate that soil biological diversity is sensitive to changes in the soil environment. This study revealed the importance of investigating the three components of soil fauna (macrofauna, mesofauna, and microfauna), since all three contribute to soil enrichment to grow nourished crops that allow plants to survive under climate change. Finally, this study may serve as a baseline to define strategies for sustainable management of tropical agricultural soils.